ALLELE FREQUENCY OF ABO AND RHESUS (Rh D) BLOOD GROUP SYSTEM AMONG THE ETHNIC STUDENTS OF LADAKH, INDIA - MURTAZA, MOHD; ALI, MD. NIAMAT; ZARGAR, MAHRUKH HAMEED (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
The ABO and Rhesus (Rh D) blood groups are the most important blood group systems among the long list of several other blood groups discovered so far. ABO and Rh D blood groups are antigenic and hereditary in nature. These blood groups are useful in the studies of population genetic to resolve medico-legal issues and more importantly the immunologic safety of blood during a transfusion. The ABO and Rh D blood groups vary globally and are not found in equal numbers among ethnic groups. The study area chosen was based on the fact that the schools enrolled students belong from all sections of the society. The blood tests were done among students after taking proper consent. The main purpose of this study was to determine the allele frequency of ABO and Rh D blood group among school students. The study found that the overall ABO allele frequency of Ia allele (p) was 0.177, Ib allele (q) 0.327 and Io allele (r) 0.494. The allele frequency of Rh factor was ID (v) (0.731) and Id (u) 0.269. This study also found that the phenotypic prevalence of blood group B was highest with the percentage of 33.7 followed by blood group A (30.4%), O (24.5%) and AB (11.25). The percentage of Rh positive was 92.71% and that of Rh negative was found to be 7.28% only.